Genetic Detection of Quinolone Resistance in Haemophilus parainfluenzae: Mutations in the Quinolone Resistance-Determining Regions of gyrA and parC - Dennis KS Law; Michelle Shuel; Sadjia Bekal; Elizabeth Bryce; Raymond SW Tsang (Canadian Journal of Infectious Diseases and Medical Microbiology)
The quinolone resistance-determining regions of gyrA and parC of both quinolone-sensitive and quinolone-resistant Haemophilus parainfluenzae strains were amplified and sequenced. Similar to Haemophilus influenzae, resistance to quinolones in H parainfluenzae is associated with mutations in the quinolone resistance-determining regions of both gyrA and parC. The present study discusses the importance of this finding.